2021
DOI: 10.30588/jmp.v11i2.892
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Reputation of Public Accounting Firms as Mediating Between Leverage, Profitability and Company Size Against Audit Delay of Large Trading Companies on Indonesia Stock Exchange

Abstract: Financial statements delivered promptly are useful in analyzing and making decisions in the economic field that can contribute to national economic growth. The timeliness of financial statements on the results of the audit report can also affect the value of the financial statements. This research aims to determine the influence of leverage, profitability, and company size on audit delay as well as the impact of the reputation of public accounting firms (KAP) as a mediating influence of leverage, profitability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 0 publications
2
8
0
Order By: Relevance
“…The research results for this hypothesis are in line with the research of (Suryandari & Dwiyanti, 2021); (Sulistiyo et al, 2022); (A. Astuti et al, 2021) who found that the reputation of public accountant firm to company size unable to reduce audit delay. In contrast to the research of (P. Astuti & Puspita, 2020); (Rahardi et al, 2021) found that the role of KAP's reputation can shorten the occurrence of audit report lag with the existence of resources and systems that support the audit process in large-scale companies.…”
Section: Results Of Hypothesis Testingsupporting
confidence: 87%
See 1 more Smart Citation
“…The research results for this hypothesis are in line with the research of (Suryandari & Dwiyanti, 2021); (Sulistiyo et al, 2022); (A. Astuti et al, 2021) who found that the reputation of public accountant firm to company size unable to reduce audit delay. In contrast to the research of (P. Astuti & Puspita, 2020); (Rahardi et al, 2021) found that the role of KAP's reputation can shorten the occurrence of audit report lag with the existence of resources and systems that support the audit process in large-scale companies.…”
Section: Results Of Hypothesis Testingsupporting
confidence: 87%
“…The implications of the size of the company on audit delay will be further strengthened by KAPs that have a good reputation because they have flexible scheduling resulting in a short span of audit delays (A. Astuti et al, 2021). Based on that explanation, the fifth hypothesis (H5) can be formulated as follows: H5: The reputation of a public accountant company has a significant role in the relationship between company size and audit report lag.…”
Section: The Role Of a Public Accountant Company Reputation In Mediat...mentioning
confidence: 99%
“…According to (A. Astuti et al, 2021), the audit delay gets shorter the longer a company has been a client of a public accounting firm . This is due to the fact that public accountants are familiar with the company's traits, internal control framework, and other factors.…”
Section: H3: Financial Distress Has a Significant Effect On Audit Rep...mentioning
confidence: 99%
“…Finally, the quality of the accounting information generated will benefit from the upkeep of a robust information technology infrastructure. Therefore, the quality of accounting information a firm generates will benefit from properly and efficiently using information technology [8]. The information technology revolution will permeate all aspects of life, including an organization's accounting information system.…”
Section: Introductionmentioning
confidence: 99%
“…Many people say that accounting information systems are nothing more than a course about computers. Accounting information systems discuss collecting data, storing data, and providing information to decisionmakers [8]. Adequate instruments are required to complete this task correctly and efficiently.…”
Section: Introductionmentioning
confidence: 99%